Necrotizing Enterocolitis: Stem Cell as Future Potential Therapy - Syafitri, Bq. Annisa Salmaadani; Manafe, Carolina Janicca Winda; Hulfifa, Lale Nandita; Aziri, Zirly Vera; Afifah, Fiza; Wahyudi, Syahla Marsellita; Musyarof, Disa Fadil (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Necrotizing enterocolitis (NEC) is an inflammatory bowel condition in infants and considered as one of the leading causes of death in infants, especially premature infants. The high mortality rate due to NEC in recent decades has become a problem because there is no current therapy that can optimally treat NEC. Currently, NEC is treated using Bell's Staging as a guide and surgery is a common procedure, especially if necrosis has occurred. However, complications arising from surgery not only reduce the patient's quality of life but can also result in death. Therefore, it is necessary to find new therapy in order to treat NEC effectively and minimize the possibility of side effects in NEC patients. Stem cells are known for their regenerative abilities which is potential to overcome tissue damage due to excessive inflammation in NEC. Previous studies also show that stem cells have become new therapy to treat other intestinal diseases which have similar features with NEC. This study aims to explain mainly on stem cells’s promising mechanism of action in treating NEC. The method used for this study is a literature review design by selecting and reviewing relevant previous literature using databases such as Google Scholar, PubMed and Science Direct. This paper summarizes pathophysiology, clinical manifestation, current therapy and mechanism of action of stem cells and their derivatives as future potential therapy for NEC. Based on evidence found, stem cells and their derivatives are potential to be used as NEC therapy in the future. However, the data obtained is not sufficient to support its use in humans. Given the urgency in finding an effective NEC management and the potency of stem cells, further research is needed to support the use of stem cells as NEC therapy.